Fluxes of CH₄ and N₂O, soil N dynamics, and microbial communities in grassland grazing systems - Rivera-Zayas, Johanie (Kansas State University, 2019)
The greenhouse gases (GHG) of nitrous oxide (N₂O) and methane (CH₄), from cattle grazing systems, need to be quantified to determine its environmental footprint. In grazed cattle systems, soil GHG fluxes dynamics respond to weather variations, soil cover, substrate availability, nutrient deposition, and land management. Soil microbial communities drive changes in carbon (C) and nitrogen (N). This study quantified N₂O and CH₄ fluxes, inorganic N dynamics, and the soil microbial community interactions in temperate and tropical grasslands. The first study, located at Konza Prairie Biological Station, measured N₂O and CH₄ fluxes from annual and 3-yr patch burned sites from summer 2014 to 2017. Measurements included GHG fluxes from static chambers, air temperature, soil water, and soil inorganic N. Emissions of N₂O were relatively low and varied as a source or a sink. Fluxes of CH₄ were a net sink. Overall, the tallgrass prairie was a small source of N₂O ranging from 9.5 to 35.9 kg CO₂-eq ha⁻¹ yr⁻¹, and a sink of CH₄ ranging from -8.0 to 51.8 kg CO₂-eq ha⁻¹ yr⁻¹. During the 3-yr period, annual burning resulted in net emissions, and 3-yr patch burning GHG sink ranged from -1.7 to -4.2 kg CO₂-eq cow/calf land unit⁻¹ yr⁻¹. Annual grassland budgets differed by year, with lower net sink during years with relatively higher precipitation. A second temperate prairie site involved a 28-d field study repeated for two years to determine the interaction between precipitation with urine and manure additions on GHG fluxes, inorganic N, and soil microbial communities. Higher N₂O (52.4 g N₂O ha⁻¹ d⁻¹) fluxes occurred under the urine treatments and ambient conditions. The N₂O sink varied from -24.0 to -0.02 g N₂O ha⁻¹ d⁻¹ with no differences between treatments. Inorganic N from urine and feces reduced the CH₄ sink from -5.9 g CH₄ ha⁻¹ d⁻¹ to emissions up to 9.1 g CH₄ ha⁻¹ d⁻¹ under high precipitation. The soil microbial community decreased within the first seven days after the urine and manure addition, and high precipitation and then increased by up to 45% within a 28 d period after the N addition or high precipitation. Overall, high precipitation and urine significantly altered soil N dynamics, causing temporary stress to the soil microbial communities, therefore altering N₂O and CH₄ fluxes. An automated static closed chamber system was used to determine the N₂O and CH₄ diurnal cycle, and the effect of sampling frequency on flux estimates. Daily average and cumulative flux are recommended to accurately estimate N₂O fluxes. The best sampling time for N₂O fluxes was between 6:00 to 12:00. During summer, biweekly sampling frequency overestimated cumulative N₂O flux. Furthermore, monthly sampling during the months of March through April overestimated CH₄ uptake. Daily, weekly, and biweekly sampling frequencies from 6:00 to 12:00 h was the most accurate method to estimate cumulative N₂O fluxes from March to August. The third experimental site located at the International Center for Tropical Agriculture in Cali, Colombia studied the effect of urine on GHG fluxes, nitrification rates, and microbial community composition in Brachiaria pastures. Ammonia-oxidizing archaea (AOA) and bacteria (AOB) qPCR analysis were used to identify the impact on nitrifier populations. Soil emissions with urine applications on Brachiaria pastures ranged from 2.1 to 11.9 g N₂O ha⁻¹ d⁻¹. Nitrification rates ranged between 0.72 to 4.5 mg N-NO₃- kg⁻¹ soil d⁻¹. Brachiaria humidicola 16888 reduced nitrification and increased arbuscular mycorrhizal fungi and actinomycetes. Overall, grasslands provide a sink for CH₄ and are a small sink or source of N₂O depending upon the weather and management practices. These fluxes are governed by nutrient dynamics and soil water. As a result, cattle grazing systems have a lower environmental footprint than previously assumed.
Keywords: Grazing systems; Environmental footprint; Soil ecology; Soil microbiology; Greenhouse gas emissions; Nitrogen cycle